Pollen and anther cultures as potential means in production of haploid kenaf (hibiscus cannabinus L.) - Dwi Susanto; Ahmed Mahmood Ibrahim; Zeti Ermiena Surya Mat Hussin (Insight, 2013)
Kenaf (Hibiscus cannabinus L.) is one of the important species of Hibiscus for human needs. It is annual upright plant that produces high biomass, has good adaptability to its environment and inexpensive to be grown. Kenaf has been cultivated in many countries since long time ago mainly for fibers. In Malaysia, however, this plant is considered new and cultivated especially in the eastern parts of Peninsular to replace tobacco plantations that have been no longer supported by the government. This plant has potential to be bred to improve the quality and the adaptability. One of the potential breeding methods to improve the plant is by the production of hybrid varieties. These varieties are superior over the inbred varieties because of the heterosis effect (hybrid vigor) ofF1heterozygous. Hybrid varieties can be produced by reciprocal combinations of crosses among homozygous lines. Homozygous lines conventionally can bachieved by repeated selfing till seven or more generations that need a lot of times. The production of haploid plants in vitro followed by chromosome doubling is a ‘short-cut’ method to produce homozygous lines in relatively short time compared to conventional methods. The objective of this study is to produce haploid lines through pollen and anther cultures in vitro. The population of haploid plantlets from this research will be induced for diploidization to produce homozygous-heterogeneous population as a basis for the production of hybrid varieties. Preliminary result showed that callus can easily be induced from the anthers compared those from the pollen grains.